A Review: Role of Bacterial Exopolysaccharides in Biofilm Formation - Kaur, Ishpreet (Journal for Research in Applied Sciences and Biotechnology, 2022)
Biofilms are a group of microbial cells that are attached to various abiotic or living surfaces and submerged in an extracellular polymeric substance produced by these microorganisms. Biofilm-producing bacteria are more resistant to antibiotics compared to planktonic cells and that is why nowadays, for the removal of pharmaceuticals from the environment biofilms are used. The presence of various substances in water sources is a major concern these days because it was observed that continuous accumulation of these active compounds in water causes harm to various aquatic organisms. Therefore, removal of these antibiotics from water bodies is compulsory and for this biofilm-producing bacteria are used in various studies. This review aims to determine that compared to planktonic cells, how bacterial biofilms are more effective for bioremediation of antibiotics from the environment.